Effects of Sterol Supplements (Cholesterol FG, Cholesterol SF, and Sterols M1M) on Growth and Survival of the Shrimp, Litopenaeus vannamei Boone. - Castille, Frank; Lawrence, Addison; Buisman, Peter; Drost, Rein (Avances en Nutrición Acuicola, 2019)
The efficacy of three sterol supplements to satisfy the dietary requirement of juvenile Litopenaeus vannamei Boone for cholesterol was evaluated in a 57-day growth trial. Sterol supplements were (1) cholesterol SF, which contained ≥91% cholesterol and ≥97% total sterol, (2) cholesterol FG, which contained ≥60% cholesterol and ≥75% total sterol, and (3) sterols M1M, which contained only 21% cholesterol and 63% total sterol. The composition of sterols other than cholesterol in M1M was similar to that in FG. Diets contained five levels of the sterol additives (0.0, 0.05, 0.1, 0.2, and 0.4%). Survival (64-91%) was not affected by either the level or type of sterol supplement. Mean weight gains ranged from 1.6 g for the base diet without sterol supplements to 7.0 g for the diet with 0.4% FG. For sterol levels above 0.05%, growth on both SF and FG was greater than on M1M. Growth increased with sterol level up to 0.4% for FG and M1M, and up to 0.2% for SF with no further increase for 0.4% SF. The growth data suggested that the cholesterol requirement for optimum growth was satisfied by either 0.16% cholesterol SF or 0.25% cholesterol FG, that the dietary requirement for cholesterol by L. vannamei was 0.15%, and that sterols other than cholesterol in FG and M1M can partially, but not completely, satisfy the dietary requirement for cholesterol.